Analysis of Language and Communication Politeness in The Globalization Era Using the Facebook Application - Rahmadani, Nadiva Putri; Difani, Nashwa Aulia; Fuaddah, Nafia; Dafa, Hikam Mahesa; Harina, Sofia Anjelita (Yayasan Sagita Akademia Maju, 2025)
This study aims to analyze the politeness of language and communication in the era of globalization, especially through the Facebook application. As the use of social media increases, interactions between individuals become more complex and diverse. Using a qualitative approach, data was collected from posts, comments and messages circulating on the platform. The results of the analysis show that language politeness on Facebook is influenced by cultural factors, communication context and user characteristics. Although politeness norms are changing and the language used tends to be more informal, there is still an element of respect. The study also reveals the challenges of maintaining politeness in a fast-paced and highly anonymous digital environment. These results are expected to provide insights into the importance of language politeness in social interactions on social media and its impact on relationships between individuals in the context of globalization.